Implementation of Islamic Education in Shaping Ethics and Morals of Early Childhood in East Kalimantan - Gianto; Sunanik (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study aims to comprehensively analyze the implementation of Islamic education in shaping the ethics and morals of early childhood in several PAUD/TK/RA institutions in East Kalimantan, which have diverse social and cultural characteristics. The main focus of this study is to examine how Islamic education strategies—including the habit of worship and good behaviour, the exemplary role of teachers as central figures, the integration of Islamic values in play-based learning approaches, and intensive collaboration between schools and parents—are applied and internalized in early childhood. The research used a descriptive qualitative approach with data collection techniques in the form of direct observation of learning activities, in-depth interviews with teachers and parents, and review of curriculum and school program documentation. The results show that Islamic education has a significant influence on children's moral development, especially in spiritual aspects (mastery of prayer and introduction to the concept of God), social aspects (polite behaviour, sharing, and cooperation), emotional aspects (ability to control emotions and communicate positively), and moral aspects (understanding of right and wrong based on Islamic teachings). In addition, consistent parental involvement is a major supporting factor in strengthening the internalization of values instilled at school. These findings confirm that structured, contextual, and continuous Islamic education in early childhood plays an important role in shaping a solid character foundation for children in the future, especially in facing social and cultural challenges in the modern era.